Pengaruh Edukasi Gizi Dengan Media Leaflet Dan Video Animasi Terhadap Tingkat Pengetahuan Anemia Pada Remaja Putri Di SMK Muhammadiyah Ambarawa Kabupaten Pringsewu 2024 - Annie Asma Wati; Alifiyanti Muharramah; Abdullah Abdullah; Masayu Dian Khairani (Journal on Education, 2024)
Anemia is a world health problem, especially in developing countries. Anemia is a condition where there is a decrease in hemoglobin levels or a decrease in the number of red blood cells circulating in the body compared to normal values ​​based on age, gender and physiological conditions. Adolescent girls are a group that is more prone to suffering from anemia than adolescent boys. Because every month young women experience menstruation, apart from that, young women often maintain their appearance and want to be thin so they go on a diet and eat less. Knowledge of young women regarding anemia is still low, namely 64.3%, so this will have an impact on preventing anemia. Other research results show that young women's knowledge about anemia The risk of anemia is still low, namely around 61%. The aim of this research is to determine the influence of animated videos as educational media on increasing knowledge about anemia among female students at SMK Muhammadiyah Ambarawa. The research design uses a quasi-experimental research design with a two group pre-test post test design. The sampling technique used was a random sampling technique with a sample size of 40 respondents, which were divided into 2 groups, namely 20 respondents for leaflet educational media and 20 respondents for animated video media. Based on the results of research that has carried out data analysis using the Wilcoxon test, there is no significant influence between leaflet media on the level of knowledge, p-value 0.008. There is a significant influence between animated video media on the level of knowledge, p-value 0.001.